Specific Egalitarianism and Total Welfare Inequality: A Decompositional Analysis - Slesnick, Daniel T. (The Review of Economics and Statistics, 1989)
Specific egalitarianism calls for the equalization in the consumption of specific commodities and is a guiding principle of redistributional policy in the United States. It is therefore of interest to evaluate the impact of specific egalitarianism on general egalitarian measures of inequality. For this purpose, multidimensional measures of welfare inequality are disaggregated into subindexes of inequality defined over the distributions of components of individual welfare. The welfare components are taken to be subutility functions identified through the two stage budgeting process. The effect of eliminating inequality in the distribution of a specific welfare component on total welfare inequality is examined for the United States. Copyright 1989 by MIT Press.